Fraternity : an inside look at a year of college boys becoming men - Robbins, Alexandra, 1976- (Dutton, 2019)
"Meet Jake, a studious new freshman weighing how far to go to find a brotherhood that will introduce him to lifelong friends and help conquer his social awkwardness; and Oliver, a hardworking chapter president trying to keep his misunderstood fraternity out of trouble despite multiple run-ins with the police. Their year-in-the-life stories help explain why students are joining fraternities in record numbers despite scandalous headlines. To find out what it's like to be a fraternity brother in the twenty-first century, Robbins contacted hundreds of brothers whose chapters don't make headlines. Brothers who suggested that many fraternities can be safe spaces for men. Fraternity is more than just an engrossing, character-driven read that includes a stunning twist. It's a vital book about the transition from boyhood to manhood; it weaves psychology, current events, neuroscience, and interviews to explore the state of masculinity today, and what that means for students and their parents. It's a different kind of story about college boys, a story in which they candidly discuss navigating identity, sex, social media, drinking, peer pressure, gender roles, and even porn. And it's a book about boys at a vulnerable age who, in a climate that can stigmatize them merely for being male, are trying to forge a path to manhood while on their own for perhaps the first time--and they don't want to navigate this complicated, coming-of-age journey alone"--